Implementation of Differentiated Learning in Islamic Religious Education in the Independent Curriculum: An Inclusive Approach - Budi Komara; Ahmad Sukandar (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the implementation of differentiated instruction models in Islamic Religious Education (IRE) within the context of the Merdeka Curriculum, employing an inclusive approach to enhance comprehension of Islamic teachings. Utilizing qualitative library research with content analysis, data were synthesized from academic literature, policy documents, and empirical studies published between 2014 and 2024. Findings reveal that differentiated instruction in IRE effectively integrates spiritual, cognitive, and social dimensions of learners, evidenced by a 25% improvement in students' ability to correlate Qur’anic verses with contemporary social issues and a 35% reduction in religion-based bullying incidents. Key challenges include educators' limited competency in designing Sharia-compliant instructional materials and cultural resistance from parents, which were mitigated through specialized training on "Maqashid Sharia-Based Differentiation" and collaborative workshops. The study proposes a Spirituo-Cognitive Differentiation Model, synthesizing personalized learning with Islamic values, which demonstrated efficacy in pilot implementations across five schools. The conclusion underscores the necessity of adaptive pedagogical frameworks aligned with Islamic principles to foster inclusive learning environments. Recommendations emphasize revising teacher training curricula to incorporate differentiated instruction modules, developing localized instructional media repositories rooted in cultural wisdom, and advancing research on artificial intelligence integration for spiritual education.